Immunochemical methods for environmental analysis : developed from a symposium sponsored by the Division of Agrochemicals at the 198th National Meeting of the American Chemical Society, Miami Beach, Florida, September 10-15, 1989 - Van Emon, Jeanette; Mumma, Ralph O.; American Chemical Society. Division of Agrochemicals; American Chemical Society Meeting (198th : 1989 : Miami Beach, Fla) (Washington, DC : American Chemical Society, 1990)
10